The Exosomal lncRNA KLF3-AS1 From Ischemic Cardiomyocytes Mediates IGF-1 Secretion by MSCs to Rescue Myocardial Ischemia-Reperfusion Injury - Chen, Gecai; Yue, Aihuan; Wang, Meixiang; Ruan, Zhongbao; Zhu, Li (Frontiers in Cardiovascular Medicine, 2021)
The purpose of the study was to explore the mechanism by which myocardial ischemia-reperfusion (I/R) injury-induced exosomes modulate mesenchymal stem cells (MSCs) to regulate myocardial injury. In this study, we established an I/R injury model in vivo and a hypoxia-reoxygenation (H/R) model in vitro. Then, exosomes isolated from H/R-exposed H9c2 cells were characterized using transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and Western blot analysis. CCK-8 assays and flow cytometry were performed to assess cell injury. ELISA was applied to determine the level of insulin-like growth factor 1 (IGF-1). Echocardiography was used to assess cardiac function in vivo. HE staining and TUNEL assays were conducted to analyze myocardial injury in vivo. In the present study, H/R-exposed H9c2 cells induced IGF-1 secretion from MSCs to inhibit cell myocardial injury. Moreover, exosomes derived from H/R-exposed H9c2 cells were introduced to MSCs to increase IGF-1 levels. The lncRNA KLF3-AS1 was dramatically upregulated in exosomes derived from H/R-treated H9c2 cells. Functional experiments showed that the exosomal lncRNA KLF3-AS1 promoted IGF-1 secretion from MSCs and increased H9c2 cell viability. In addition, miR-23c contains potential binding sites for both KLF3-AS1 and STAT5B, and miR-23c directly bound to the 3'-UTRs of KLF3-AS1 and STAT5B. Furthermore, the lncRNA KLF3-AS1 promoted IGF-1 secretion from MSCs and rescued myocardial cell injury in vivo and in vitro by upregulating STAT5B expression. The lncRNA KLF3-AS1 may serve as a new direction for the treatment of myocardial I/R injury.